Photorespiration in Air and High CO(2)-Grown Chlorella pyrenoidosa - Shelp, Barry J. (1981)
Oxygen inhibition of photosynthesis and CO(2) evolution during photorespiration were compared in high CO(2)-grown and air-grown Chlorella pyrenoidosa, using the artificial leaf technique at pH 5.0. High CO(2) cells, in contrast to air-grown cells, exhibited a marked inhibition of photosynthesis by O(2), which appeared to be competitive and similar in magnitude to that in higher C(3) plants. With increasing time after transfer to air, the photosynthetic rate in high CO(2) cells increased while the O(2) effect declined. Photorespiration, measured as the difference between (14)CO(2) and (12)CO(2) uptake, was much greater and sensitive to O(2) in high CO(2) cells. Some CO(2) evolution was also present in air-grown algae; however, it did not appear to be sensitive to O(2). True photosynthesis was not affected by O(2) in either case. The data indicate that the difference between high CO(2) and air-grown algae could be attributed to the magnitude of CO(2) evolution. This conclusion is discussed with reference to the oxygenase reaction and the control of photorespiration in algae.